ANALISIS PERLINDUNGAN HUKUM TERHADAP NAMA DOMAIN DI INTERNET - Virhani, Mohan Rifqo (Kementerian Komunikasi dan Informatika R.I., 2011)
The method used in this study is qualitative. These data were collected through literature study, observation and used question research through email to informan. Legal protection of domain names in the media Internet is very weak, if can be seen of law system, such as substance of law, structure of law and legal culture. These components should be strengthened to provide legal protection of domain names in the media internet. Keywords: substance oflaw, structure oflaw, legal culture